Penilaian Teknologi Menggunakan Metode Teknometrik pada Industri Pengolahan Pangan - Nurrizki, Diza; Shafira, Alvinia; Aurellia, Azarine Faustina; Wiratmadja, Iwan Inrawan (Journal of Research in Industrial Engineering and Management, 2024)
The development of micro, small, and medium-sized enterprises (MSMEs) is on the rise and is considered flexible in seizing existing opportunities. Furthermore, the increasingly competitive global environment demands that MSMEs enhance their competitiveness to maintain their existence. In this era of rapid trade development, the role of technology is crucial to success. Technology is one of the main competitive advantages for MSMEs, and improving technological capabilities forms the foundation for enhanced business performance. However, MSMEs often face the challenge of limited knowledge regarding the selection of technology that supports their formulated corporate strategy. The research objective is to analyze technology assessment and formulate effective technology strategies to support the development of X MSME. The method used is the technometric method to assess business competitiveness and formulate effective technology strategies. This method was developed by UNESCAP and consists of four technology components, namely technoware, humanware, infoware, and orgaware. The Total Composite Index (TCC) value obtained is 0.478. The sophistication level values of the technoware component are 0.297, humanware is 0.533, infoware is 0.315, and orgaware is 0.531. In benchmarking, X MSME falls below its competitors in terms of overall components. According to the Sethi’s technology strategy formulation, X MSME is positioned in the Draw quadrant.